Hydrogen adsorption on porous silica - Sheppard, Drew; Buckley, Craig (Pergamon-Elsevier Science Ltd, 2008)
A number of MCM-41 samples were produced with different ageing times and zinc dopantlevels. Hydrogen adsorption experiments performed at 77K on pure MCM-41 samplesshowed a maximum excess wt% uptake of 2.01%. Samples were doped with Zn in the Si:Znratio of 50:1, 25:1 and 10:1. These samples showed an increase in d-spacing in their XRDpatterns, suggestive of Zn incorporation into the structure but resulting in a decrease inlong range pore ordering and surface area with increasing Zn content. Two of the threedoped samples showed an increase in H2 adsorbed per unit surface area suggestive ofincreased interaction strength. However, definitive confirmation is difficult due todegradation of the pore structure and surface area. Adsorption at room temperature wasminimal, being 0.1wt% or below.